microRNA Expression in Women With and Without Polycystic Ovarian Syndrome Matched for Body Mass Index - Butler, Alexandra E.; Ramachandran, Vimal; Sathyapalan, Thozhukat; David, Rhiannon; Gooderham, Nigel J.; Benurwar, Manasi; Dargham, Soha R.; Hayat, Shahina; Hani Najafi-Shoushtari, S.; Atkin, Stephen L. (Frontiers in Endocrinology, 2020)
Background. Despite several authors who have hypothesized that alterations of small noncoding RNAs (miR) are implicated in the etiopathogenesis of PCOS, contrasting findings have been reported so far. Discrepancies in BMI levels may account for these differences; therefore, the aim of the present study was to determine whether miR differed in serum samples collected from age and BMI matched control and PCOS women. Methods. In a cross-sectional study, miR were measured using quantitative polymerase chain reaction in 29 women with anovulatory PCOS and 29 control women who were in the follicular phase of their menstrual cycle, from the local biobank. Results. 176 miR were detected, of which 15 miR passed the false discovery rate (FDR p<0.05) that differed between PCOS women and control women. There was no association of the top 9 miR (p<0.02) (miR-486-5p, miR-24-3p, miR-19b-3p, miR-22-3p, miR-19a-3p, miR-339-5p, miR-185-5p, miR-101-3p, miR-let-7i-5p) with body mass index (BMI), androgen levels, insulin resistance or anti-mullerian hormone (AMH) in either PCOS or normal women. Ingenuity pathway assessment showed the pathways were interrelated for abnormalities of the reproductive system. Conclusion. When the confounding influence of weight was accounted for, miR levels differed between anovulatory PCOS women and control women in the follicular phase of the menstrual cycle. Interestingly, the differing miR associated with the pathways of reproductive abnormalities, but did not associate with AMH or metabolic parameters.